A judicialização da política pública de medicamentos : o direito à saúde entre a dignidade e a equidade - Lopes, Nairo José Borges (2014)
The judicialization of health services is a controversial topic since it has huge impacts on public management. This study analyses the judicialization of pharmaceutical policy focusing on how two alternative justifications of the right to health interfere on the tension between the executive and the judicial powers. It is a review of the pertinent literature and a theoretic analysis of two approaches to the right to health, the one based on human dignity and the one based on equity. The central hypothesis defended here is that human dignity is not the most adequate justification to define state obligations on health issues, given that it is suitable to be taken as an absolute value, what may lead to injustices. Thus, judicial sentences based on it  may interfere unjustifiably on decisions of other institutions, since they do not take account of some important features of the public health system. Besides the introduction and the concluding remarks, the study has three chapters. The first one describes the main lines of the Brazilian health system, especially  its pharmaceutical policy, and exposes the phenomenon of the judicialization of health policy. The second and third chapters describe and examine the justifications based on dignity and equity, respectively, and their role in deciding which obligations must be included on the right to health. The third chapter also investigates possible distributive problems related to the judicialization of health services. The conclusion is that, although human dignity should not be totally ignored as a social parameter, it also should not be the criterion to distribute goods in the domain of health policy, given that it ignores the need to avoid unnecessary and unfair inequalities, the role of the social determinants of health and the scarcity of resources. Therefore, equity should be the overriding criterion in judicial decision making on pharmaceutical policy.